Cyber Law Unveiled: Insights from Scholarly Discourse - Alivia, Afrida Dewi; Purwaningsih, Sri Budi; Prasetyo, Suyo Gigih (Proceedings of The ICECRS, 2023)
This data article presents a comprehensive analysis of scholarly publications in the realm of Cyber Law and Fixed Effects Panel Models, sourced from Lens.org. The study focused on articles encompassing "Cyberlaw OR Cyber Law AND Fixed Effects Panel Models," employing rigorous filters for document type and subject matter, specifically Law. Our analysis delves into multiple facets of this domain, including Top Institution Name, Scholarly Works Over Time, Top Fields of Study, Fields of Study covered by the most active Institutions, Most Active Authors, Scholarly Works Scatter Plot, Most Active Countries/Regions, Top Publisher, and Top Journals by Publisher. The primary objective was to unravel intricate patterns within Cyber Law research and discern key contributors and their thematic interests. Results revealed leading institutions such as London School of Economics and Political Science, dynamic trends over decades, and interdisciplinary intersections with fields like Economics and Sociology. Notable authors and prolific journals were identified, underscoring the vibrancy of this academic domain. This data provides valuable insights for scholars, students, and policymakers, fostering a deeper understanding of Cyber Law's evolving landscape and encouraging interdisciplinary collaborations for future research endeavors. Highlights : Institutional Dynamics: Uncovering leading institutions shaping Cyber Law discussions, essential for academic collaborations and knowledge dissemination. Temporal Patterns: Analyzing scholarly works over time, highlighting key publication years and identifying enduring topics within Cyber Law research. Intersections: Revealing collaborative intersections with fields like Economics and Sociology, emphasizing the multidisciplinary nature of Cyber Law scholarship. Keywords: Cyber Law, Fixed Effects Panel Models, Scholarly Publications, Academic Trends, Interdisciplinary Research